2020
DOI: 10.1021/acs.iecr.0c01891
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of an Encapsulated Surfactant System, ESS, via β-CD Host–Guest Interactions to Inhibit Surfactant Adsorption onto Solid Surfaces

Abstract: In this work, the issue of surfactant adsorption (SA) onto solid surfaces was attempted through surfactant encapsulation via host−guest interactions using β-CD. Formulations of a nonencapsulated surfactant system (Non-ESS) and an encapsulated surfactant system (ESS) were obtained through phase behavior analysis. Rheology shows that the ESS and Non-ESS display low viscosities, shear-thinning flow behavior, and structural stability. The ESS and Non-ESS were applied as surfactant flooding for enhanced oil recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The authors observed that surfactant encapsulation effectively prevents surfactant loss due to adsorption onto solid surfaces and maintains the integrity of the surfactant mass flowing through sand-based porous media systems. 316 The CD cavity exhibits the capability to release surfactant molecules and encapsulate oil molecules owing to its pronounced hydrophobic nature. Consequently, the encapsulated surfactant is liberated from the cavity, allowing it to penetrate the pores of the formation and perform its designated functions.…”
Section: Polymeric Surfactantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors observed that surfactant encapsulation effectively prevents surfactant loss due to adsorption onto solid surfaces and maintains the integrity of the surfactant mass flowing through sand-based porous media systems. 316 The CD cavity exhibits the capability to release surfactant molecules and encapsulate oil molecules owing to its pronounced hydrophobic nature. Consequently, the encapsulated surfactant is liberated from the cavity, allowing it to penetrate the pores of the formation and perform its designated functions.…”
Section: Polymeric Surfactantsmentioning
confidence: 99%
“…This study highlighted the importance of the encapsulator (carrier) in the EOR system. The authors observed that surfactant encapsulation effectively prevents surfactant loss due to adsorption onto solid surfaces and maintains the integrity of the surfactant mass flowing through sand-based porous media systems . The CD cavity exhibits the capability to release surfactant molecules and encapsulate oil molecules owing to its pronounced hydrophobic nature.…”
Section: Eor Surfactant Carriersmentioning
confidence: 99%
“…It is evident that the formation of micelles initiates at higher concentrations of surfactants, leading to the creation of hemimicelles consisting of one or two layers of surfactant molecules [ 255 , 256 ]. After the solid surface has been coated with this layer, the adsorption process continues until a complete bilayer is formed [ [257] , [258] , [259] ]. To enhance the adsorption of the surfactant onto solid surfaces, it is essential to anchor the molecules at the interfaces between liquid-liquid or liquid-air [ 260 , 261 ].…”
Section: Nanoparticle Utilization In the Oil And Gas Industrymentioning
confidence: 99%
“…Massarweh and Abushaikha (2020) reviewed the use of surfactants in EOR in 2020, they found that the surfactants have successfully increased the oil recovery through interfacial tension reduction, wettability alteration, foam generation, and emulsification. Also, several papers use formulations or synergistic combinations of surfactants to enhance the performance of EOR (Belhaj et al, 2021; Cui et al, 2012; Jian et al, 2018; Liu et al, 2018; Romero‐Zerón et al, 2020; Sarkar et al, 2021; Sarmah et al, 2019). However, since 2010, supramolecular surfactants have been developed and employed.…”
Section: Introductionmentioning
confidence: 99%